2021
DOI: 10.3952/physics.v61i3.4519
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spring grass fires on indoor air quality in air-conditioned office building

Abstract: Open biomass burning (OBB) is a significant air pollution source, but it is still not clear to what extent OBB events affect indoor air quality [1]. Outdoor and indoor measurements of submicron particulate matter (PM1) were conducted on 25–29 April (2019) in the capital city Vilnius (Lithuania). Fires from neighbouring countries (Belarus, Ukraine and Russia) and in the vicinity of Vilnius broke out during the measurement campaign. The temporal evolution and transport of OBB plume were investigated by combining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The respective CR values for adults were 2.7 × 10 −5 , 1.3 × 10 −9 and 1.1 × 10 −4 , indicating significant risk for dermal contact [17]. On the other hand, a study in Vilnius, Lithuania showed that despite the much lower fine PM 1 concentration indoors than outdoors (8.8 ± 2.7 µg m −3 against 43.2 ± 22.3 µg m −3 ) during forest fire events, the highly acidic indoor PM 1 could have harmful health effects [101], thus highlighting the importance of aerosol PH in healthrelated studies. Furthermore, it should be noted that apart from the PTEs that are examined in this work, many other components of PM, such as VOCs, formaldehyde and carbon monoxide (CO), may negatively affect air quality and human health indoors [102,103].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…The respective CR values for adults were 2.7 × 10 −5 , 1.3 × 10 −9 and 1.1 × 10 −4 , indicating significant risk for dermal contact [17]. On the other hand, a study in Vilnius, Lithuania showed that despite the much lower fine PM 1 concentration indoors than outdoors (8.8 ± 2.7 µg m −3 against 43.2 ± 22.3 µg m −3 ) during forest fire events, the highly acidic indoor PM 1 could have harmful health effects [101], thus highlighting the importance of aerosol PH in healthrelated studies. Furthermore, it should be noted that apart from the PTEs that are examined in this work, many other components of PM, such as VOCs, formaldehyde and carbon monoxide (CO), may negatively affect air quality and human health indoors [102,103].…”
Section: Discussionmentioning
confidence: 98%
“…This practice is also necessary during pollution events caused by accumulation of pollutants due to excess emissions and/or unfavorable meteorological conditions, such as calms, shallow boundary layer and temperature inversions. On the other hand, air filtering systems could be especially efficient in removing fine particulate from indoor air [101,107]. For new energy-conserving buildings in Asaluyeh, special treatment should be given to the ventilation options and in reducing exchanges between outdoor and indoor air in a way to limit health risk [108][109][110].…”
Section: Mitigation Strategies and Future Projectionsmentioning
confidence: 99%